Diabetes protects from prostate cancer by downregulating androgen receptor: new insights from LNCaP cells and PAC120 mouse model. - Anna Barbosa-Desongles; Cristina Hernández; Ines De Torres; Francina Munell; Marie-France Poupon; Rafael Simó; David M Selva (PLoS ONE, 2013)
Type 2 diabetes has been associated with decreased risk of prostate cancer in observational studies, and this inverse association has been recently confirmed in several large cohort studies. However the mechanisms involved in this protective effect remain to be elucidated. The aim of the present study was to explore whether different features of type 2 diabetes (hyperinsulinemia, hyperglycemia and tumor necrosis factor alpha [TNF-α]) protect against the development of prostate cancer. For this purpose LNCaP cells were used for in vitro experiments and nude mice in which PAC120 (hormone-dependent human prostate cancer) xenografts had been implanted were used for in vivo examinations. We provide evidence that increasing glucose concentrations downregulate androgen receptor (AR) mRNA and protein levels through NF-κB activation in LNCaP cells. Moreover, there was a synergic effect of glucose and TNFα in downregulating the AR in LNCaP cells. By contrast, insulin had no effect on AR regulation. In vivo experiments showed that streptozotocin-induced diabetes (STZ-DM) produces tumor growth retardation and a significant reduction in AR expression in PAC120 prostate cancer mice. In conclusion, our results suggest that hyperglycemia and TNF-α play an important role in protecting against prostate cancer by reducing androgen receptor levels via NF-κB.